Notes on the contradictions of housing policy in Latin America today: the situation in Brazil and Venezuela - Mioto, Beatriz Tamaso; Aruto, Pietro Caldeirini (Revista Brasileira de Estudos Urbanos e Regionais, 2015)
The production of housing is an important activity for capitalist accumulation and one of the foci of conflict around the appropriation of space. Historically, this required state regulation by various means, including, housing policies. Although it is something present in all socio-spatial formations, the way in which production and regulation of the sector take place in different spaces depends, at bottom, on the ongoing accumulation pattern. Based on this methodological assumption, this article seeks is, in the light of the critical theory of underdevelopment, to analyze the current characteristics and limitations of housing policies in the continent of Latin America. Given the variety of ongoing experiences, the discussion will be centered on the Minha Casa Minha Vida (My House My Life) (Brazil) and Gran Misión Vivienda (Venezuela) programs as being two paradigmatic models of the production of a city. It is said that there are three main differences between these two programs: the subsidy schemes and funding instruments; land policy; and the state's relationship with the fractions of capital that determines the pattern of the policies of the countries.